Managing soft skills development in vocational higher education: A case study of institutional practices in Indonesia - Syukri Fathudin Achmad Widodo; Sudji Munadi; Chrisna Tri Harjanto; Tri Adi Prasetya; Betania Kartika Muflih (Jurnal Pendidikan Vokasi, 2025)
The demands of the workplace in the Industry 4.0 era require vocational education to produce graduates who not only master technical skills but also possess non-technical (or "soft") skills, such as communication, teamwork, adaptability, and problem-solving. This study aims to identify and analyze effective institutional practices in developing soft skills in vocational higher education. This research employs a qualitative case study approach, using semi-structured interviews with department heads, study program heads, and lecturers at two State polytechnics in Indonesia. Thematic analysis reveals that soft skills development is implemented through four primary strategies: student orientation, internal training, external training with industry, and integration into the curriculum. These four strategies form a holistic institutional model to strengthen students' personal and professional readiness for the workplace. The research findings emphasize the importance of systematic management of soft skills development to produce vocational graduates who are technically competent, possess strong character, and are highly competitive.